DDVP (Shell Dichlorvos) for pregnant sows - B A Koch; Robert H Hines (Kansas Agricultural Experiment Station Research Reports, 1969)
Most recent laboratory and research station reports have indicated that 2,2 - dichlorovinyl dimethyl phosphate (DDVP) (Shell Dichlorvos) fed at low levels to pregnant sows in late gestation favorably affects newborn pigs. A field study we reported last year showed no favorable effect among over 200 litters. More than 600 barrows were checked at slaughter and no difference was detected in slaughter age between pigs from treated or untreated sows. Trials reported here involve sows and gilts in the K-State research swine herd. Trial 1 was those farrowing in March; trial 2, those farrowing in May.; Swine Day, Manhattan, KS, September 25, 1969
Keywords: Swine day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 151; Swine; DDVP (Shell Dichlorvos); Pregnant sows